Alinhamento estratégico em construtoras cearenses - Costa, George Silva (2010)
The alignment concept has been gaining strength since the competitive market in which the then inserted companies, they can not waste their resources poorly formulated strategies, processes that do not meet the needs of customers or people who do not understand or do not contribute to the achievement the company's strategy. In construction companies that reality is no different, the competition has been shown to be relevant. The rationale for this work relates to the importance of the strategy in the competitive environment and the difficulty of deriving operationalization of the complexity of the formulation and implementation process and the limited number of studies on the topics: strategic alignment and strategy in construction. This work is classified as exploratory, as it develops studies that give an overview of the fact or phenomenon studied. Such research is to analyze what the internal strategic alignment in construction from the development of a method for analyzing, measuring and comparing / viewing the strategic alignment in construction companies, focusing on competitive strategy and manufacturing strategy, highlighting that the competitive criteria prioritized in companies. There were case studies in three builders in the city of Fortaleza / CE. Analyzed companies from the method developed, reaching the alignment degree in each, allowing for comparison and better visualization of the results. Finally, we present the main findings of the study, the method developed, and suggestions for future research, for example, to apply the model in other companies, in order to improve understanding and collaborate with propositions on the above subject, as as seeking to explain why the different views between the representatives within the same company and the real potential consequences of this distortion of priorities and their impact on company performance.